STUDY ON IN PLANTA TRANSFORMATION IN MAIZE - Trình, Đinh Văn (Vietnam Journal of Biotechnology, 2011)
Almost fransformation methods in maize (Zea mays L.) require multiple tissue culture manipulations that are time-consuming and expensive. Furthermore, these only can apply to a few highly regenerative genotypes. The first time in Vietnam, we applied a simple in planta method that makes it possible to fransfer commercial variety through female reproductive system. The Agrobacterium tumefaciens sfrain EHA105 which contains plasmid pBig.ubi carrying drought tolerant gene - ZmDREBlA and hygromycin resistant gene - hpt was used. Maize’ silks (female flowers) were isolated and applied with bacterium suspension before pollinating with the pollens ofthe same cultivars. 135 ears (13145 kemels) of TQ harvested in the winter-spring crop 2006 - 2007. The fransgenic seedlings at 2 - 3 leaves state were selected by drought sfress. Hygromycin resistant assay and PCR analysis on 59 plants (To) survived after drought selection showed the transformation efficiency of TQ plants was 0.023%.